2020
DOI: 10.1183/20734735.0322-2019
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer incidence and mortality with extended follow-up in the National Lung Screening Trial

Abstract: @ERSpublicationsThe extended follow-up of the NLST represents a timely and important update to the NLST data, alongside full results of the NELSON and the LUSI trials, as Europe begins to set out a vision for lung cancer screening. http://bit.ly/2MYXedI Affiliations

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 10 publications
0
4
1
Order By: Relevance
“…The overall detection rate of lung cancer in this study was 1.8%, which was higher than those in the NLST (1.1%) (36) and NELSON (0.9%) (6) studies, with age and smoking history as inclusion criteria. However, it was similar to screening studies of non-smoking women (10,13,37).…”
Section: Discussioncontrasting
confidence: 65%
“…The overall detection rate of lung cancer in this study was 1.8%, which was higher than those in the NLST (1.1%) (36) and NELSON (0.9%) (6) studies, with age and smoking history as inclusion criteria. However, it was similar to screening studies of non-smoking women (10,13,37).…”
Section: Discussioncontrasting
confidence: 65%
“…Current evidence suggests that the 5-year survival rate of patients with early or intermediate-stage lung cancer (more than 70%) is significantly higher than late-stage lung cancer (less than 15%) (4). Therefore, early screening, diagnosis and treatment of lung cancer can significantly improve patient survival and prognosis (1,(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…In clinical practice, low-dose computed tomography (LDCT), positron emission tomography/computed tomography (PET/CT) and tumor biomarkers are commonly used to screen solitary pulmonary nodules (SPNs) (4,(7)(8)(9)(10). It has been reported that the false positive rate of high-resolution computed tomography (HRCT) is 96.4% (4), which makes it difficult to ascertain the nature of pulmonary lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Metastasis in lung cancer is the major reason leading to mortality of lung cancer patients. Although the application of the Lung Screening Trial (low dose helical computed tomography, LDCT) with chest radiography allows lung cancer to be diagnosed at an early stage, the prognosis of metastatic lung cancer is still unpromising even if combining surgery with radiotherapy, chemotherapy, immunotherapy and gene-targeted drug therapy [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%